2015
DOI: 10.4322/0104-4931.ctoao440
|View full text |Cite
|
Sign up to set email alerts
|

A estratégia grupal na reabilitação de pessoas com acidente vascular cerebral: Reflexões sobre a prática da Terapia Ocupacional

Abstract: Group strategy in the rehabilitation of people with stroke: Reflections about the occupational therapy practice Abstract:The present study aimed to analyze the use of a group, treated by Occupational Therapy, as a strategy for the rehabilitation of adults with sequelae resulting from stroke. The group strategy was developed at the Center for Teaching and Research of the University of São Paulo -USP from August 2009 to October 2010. This is a qualitative and descriptive study based on the documental analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
1
0
2
Order By: Relevance
“…A experiência do emprego de grupos pela Terapia Ocupacional tem demonstrado a exploração de possibilidades terapêuticas de diversas naturezas, salientando que os benefícios se estendem da elaboração do significado da experiência da incapacidade, conscientização dos limites, melhora das capacidades corporais e suporte emocional (Antônio & Toldrá, 2015). Segundo Malta e Merhy (2010), no que diz respeito às doenças crônicas, é importante que a participação em grupos faça sentido e que propicie a criação de novos significados para o viver, como podemos perceber pela iniciativa dos pacientes no cuidado com a aparência, nas oficinas.…”
Section: Resultsunclassified
“…A experiência do emprego de grupos pela Terapia Ocupacional tem demonstrado a exploração de possibilidades terapêuticas de diversas naturezas, salientando que os benefícios se estendem da elaboração do significado da experiência da incapacidade, conscientização dos limites, melhora das capacidades corporais e suporte emocional (Antônio & Toldrá, 2015). Segundo Malta e Merhy (2010), no que diz respeito às doenças crônicas, é importante que a participação em grupos faça sentido e que propicie a criação de novos significados para o viver, como podemos perceber pela iniciativa dos pacientes no cuidado com a aparência, nas oficinas.…”
Section: Resultsunclassified
“…[ 8 ] The interaction between participants increases self-esteem, improves functional capacity and performance in important activities, and establishes social relationships, helping them overcome their difficulties. [ 9 ] In a randomized clinical trial by Doussoulin et al, [ 8 ] group-based CIMT participants reported that the format allowed them to interact with individuals with similar disabilities and obtain feedback on their experiences, in addition to providing an opportunity for collaborative work, which influenced their functional independence at home and in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Assim, o acompanhamento terapêutico ocupacional de forma grupal pode se apresentar como uma estratégia de intervenção eficaz de reabilitação e de superação das limitações decorrentes da própria deficiência, na medida em que estimula a troca de aprendizados e experiências sobre práticas de autocuidado entre as pessoas (ANTONIO;TOLDRÁ, 2015), bem como potencializa o uso de diferentes estratégias terapêuticas (TAVARES et al, 2012).…”
Section: Introductionunclassified